Discuss: Several Problems in the Chinese Ancient History Textbook of Zhu Shaohou Version - Yao, Jianguang; Chen, Lingfei (Advances in Social Sciences Research Journal, 2023)
The textbook Ancient History of China edited by Zhu Shaohou and others is the most widely used textbook for the course "Chinese ancient history" of history majors in Chinese universities. This textbook has been revised multiple times in the past 40 years, but there are still many problems, such as contradictory expressions of the same problem, lack of pronunciation and meaning labeling of rare characters in ancient literature, omission of legal and diplomatic aspects in the history of Song and Yuan , inaccurate use of historical materials, and obvious untrue statements; Part of the content is outdated, neglecting the important role of maps, schematics, datasheets, and physical photos in students' construction of specific historical time and space and understanding of relevant content. These issues reveal that there is room for improvement at all stages of the compilation process of undergraduate history textbooks in Chinese universities, and it is urgent to attract the attention of the historical community and management departments.